The impact of early nutritional interventions on growth and development in infants- Meta-analysis - Abdulghani, Dina W. (International Journal of Innovative Research and Scientific Studies, 2025)
Early childhood nutrition is critical for long-term growth, cognitive development, and overall health. This meta-analysis evaluates the impact of nutritional interventions on growth outcomes in children under 8 years, focusing on BMI-for-age, weight-for-height, height-for-age, and weight-for-age z-scores. A systematic search of PubMed, Embase, and Cochrane Library databases identified 429 studies, with 8 randomized controlled trials (n = 6,645 children) meeting inclusion criteria. Pooled mean differences (MDs) and 95% confidence intervals (CIs) were calculated for growth outcomes, with subgroup analysis by intervention duration. Heterogeneity was assessed using I² statistics. Nutritional interventions showed no significant effects on BMI-for-age (MD = 0.12, 95% CI: −0.07, 0.30) or height-for-age (MD = 2.45, 95% CI: −0.79, 5.70). For weight-for-height and weight-for-age, interventions lasting ≥6 months yielded modest improvements (MD = 0.36, 95% CI: 0.00, 0.72 and MD = 2.23, 95% CI: 0.01, 4.44, respectively), while shorter interventions had no impact. High heterogeneity (I² > 99%) indicated variability in intervention designs and contexts. Sustained nutritional interventions (≥6 months) modestly improved weight-related outcomes but had no significant effect on linear growth or BMI. Context-specific, long-term strategies combining nutrition education, supplementation, and socioeconomic support are recommended to effectively address childhood malnutrition. Policymakers and practitioners should prioritize sustained, multifaceted interventions to maximize impact on child growth outcomes.